Archival data review of intimate partner homicide-suicide in Jamaica, 2007 - 2017: focus on mental health and community response - Audrey M. Pottinger; Althea Bailey; Nickiesha Passard (Pan American Health Organization, 2019)
Objective. To identify social and behavioral patterns and mental health concerns associated with intimate partner homicide-suicide (IPHS) in Jamaica through an analysis of media and police reports. Methods. This was an archival data review of police records and print, radio, and television reports of IPHS incidents from January 2007 - June 2017 in Jamaica. The 27 cases found were qualitatively analyzed using pre-identified codes and open coding to generate themes and patterns. Results. A prevalence rate of 0.1 per 100 000 was determined. In all cases, males were the homicide-offender. Sociodemographic patterns associated with IPHS incidents-age, personality traits, choice of weapon, and time of occurrence-were consistent with previous findings. Common triggers were offender obsession, sexual jealousy, and fear of separation. Despite reports of mental health concerns in both male and female partners, neither the couples nor community members sought help prior to the homicide-suicide. Conclusion. These findings demand a change in cultural attitudes toward domestic disputes and mental health concerns, and a redefining of the community's responsibility in IPHS. The warning signs associated with IPHS should be part of existing violence and suicide prevention programs.